2017
DOI: 10.1089/hum.2017.121
|View full text |Cite
|
Sign up to set email alerts
|

Improvement ofIn VivoExpression of Genes Delivered by Self-Amplifying RNA Using Vaccinia Virus Immune Evasion Proteins

Abstract: Among nucleic acid–based delivery platforms, self-amplifying RNA (saRNA) vectors are of increasing interest for applications such as transient expression of recombinant proteins and vaccination. saRNA is safe and, due to its capability to amplify intracellularly, high protein levels can be produced from even minute amounts of transfected templates. However, it is an obstacle to full exploitation of this platform that saRNA induces a strong innate host immune response. In transfected cells, pattern recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“… 42 For example, it was demonstrated for self-amplifying mRNA that potent initial induction of type I interferons by double-stranded RNA (dsRNA) was counterproductive to immunogen expression and subsequent immunogenicity. 83 , 84 Thus, any rational exploitation of the innate signals and/or immunomodulation will require careful evaluation, which will ultimately need to be confirmed in the target species, i.e., humans. 85 Nevertheless, new technologies can often precipitate the long-awaited breakthroughs in difficult challenges of public health, such as prevention and treatment of HIV-1, malaria, tuberculosis, cancer, and allergies, and the mRNA platform has the potential to be such a transforming technology.…”
Section: Discussionmentioning
confidence: 99%
“… 42 For example, it was demonstrated for self-amplifying mRNA that potent initial induction of type I interferons by double-stranded RNA (dsRNA) was counterproductive to immunogen expression and subsequent immunogenicity. 83 , 84 Thus, any rational exploitation of the innate signals and/or immunomodulation will require careful evaluation, which will ultimately need to be confirmed in the target species, i.e., humans. 85 Nevertheless, new technologies can often precipitate the long-awaited breakthroughs in difficult challenges of public health, such as prevention and treatment of HIV-1, malaria, tuberculosis, cancer, and allergies, and the mRNA platform has the potential to be such a transforming technology.…”
Section: Discussionmentioning
confidence: 99%
“…116 The usage of modified nucleosides to silence self-amplifying mRNA recognition by innate immune sensors is not an option, because it could impair RDRP-mediated mRNA amplification in target cells, and the effect of modified nucleoside would also be lost after the first round of amplification. Beissert et al 117 have demonstrated that antigen expression from self-amplifying mRNA can be significantly improved in vitro and in vivo by co-transferring mRNAs encoding IFN and PKR inhibitory proteins, such as viral protein B18R from vaccinia virus. These data are consistent with previous results showing an increase in translation from an alphavirus self-amplifying mRNA co-expressing a dominant-negative PKR 118 or co-delivered with a recombinant vaccinia B18R protein.…”
Section: Self-amplifying Mrna Vaccinesmentioning
confidence: 99%
“…The innate immune response against exogenous mRNA can be minimized by avoiding the activation of TLR receptors, by using highly purified transcripts (complete removal of production byproducts, such as dsRNA and DNA template) and modified nucleosides (replacing uridine for pseudouridine) [25,62]. Another strategy is to suppress the receptors by co-expressing mRNA encoding immune evasion proteins, such as vaccinia virus proteins E3, K3, and B18 [64][65][66]. These proteins can locally and temporarily suppress PKR and IFN pathway activation and enhance expression of mRNA-encoded genes of interest.…”
Section: Induction Of the Innate Immune Response By Mrna Vaccinesmentioning
confidence: 99%